E-119 Predictors of first pass efficacy in posterior circulation acute ischemic strokes. (23rd July 2022) - Hafeez, M; Essibayi, M; Raper, D; Al Kasab, S; Burks, J; Alsbrook, D; Park, M; Dumont, T; Townsend, R; Starke, R; Arthur, A; Goyal, N; et al.
Abstract : Introduction: First-pass efficacy (FPE), defined as achieving complete or near-complete revascularization of an occluded vessel with first attempt, has recently emerged as an important angiographic predictor of successful endovascular thrombectomy (ET) in acute ischemic strokes (AIS). There is growing evidence that FPE is associated with better clinical outcomes. However, its predictors and clinical outcomes in posterior circulation AIS (pcAIS) remain under-explored. In this study, we investigate the efficacy of ET and address the clinical, radiological, and procedural predictors of FPE in pcAIS. Methods: Patients with pcAIS from the Thrombectomy and Aneurysm Registry (STAR) were included. Baseline characteristics and clinical outcomes were evaluated by first-pass outcomes under two groups: FPE and non-FPE. FPE was defined as modified Thrombolysis and Cerebral Infarction (mTICI) score > 2c after first pass of ET. Baseline characteristics included demographic, clinical and procedural variables, initial CT Angiogram (CTA) findings, composite scores for collateral circulation (BATMAN score) and clot burden (pc-CTA score). Clinical outcomes included 90-day modified Rankin Scale (mRS) score, National Institutes of Health Stroke Scale (NIHSS) score, distal emboli, symptomatic intracranial hemorrhage (sICH), and mortality. FPE predictors were assessed via univariate (UVA) and multivariate (MVA) logistic regressions. Results: A total of 363 patients with pcAIS received ET between 2012 and 2020. 179 out of 354 (49%) patients achieved FPE. Mean time to revascularization (puncture to revascularization) was significantly shorter (40 vs 70.1 minutes; P <0.001) in the FPE group. Direct aspiration was more frequently utilized in non-FPE group (27.4% vs 34.2%; P=0.026). Patients with successful FPE showed higher rates of final angiographic revascularization represented by mTICI > 2b in 88.6% (non-FPE: 72.6.1%; p < 0.001) and mTICI > 2c in 94.4% (non-FPE: 73%; p < 0.001). Discharge mean mRS (4.5 vs 3.5; p < 0.001) and 90-day mRS (4.2 vs 3.1; p < 0.001) were significantly better in patients who achieved FPE. Complication rates among both outcome groups were non-significantly different, except for distal emboli rate, which was more common in the non-FPE (10.8% vs 3.2%; P=0.037). On UVA, prior history of AIS was associated with decreased odds (OR: 0.52; P=0.04) while atrial fibrillation was associated with increased odds (OR: 2.06; P= 0.005) of FPE, which remained significant on MVA (OR: 1.92; P=0.022). Conclusion: FPE is a crucial predictor of successful ET in pcAIS, emphasizing the FPE and faster revascularization as role players in clinical outcomes of pcAIS. Atrial fibrillation and previous AIS independently predict FPE. The discrepancy in FPE rates by clot composition is illustrated by the higher rates of FPE in atrial fibrillation patients. Therefore, future histological and clinical studies are warranted to further address the clinical features of ischemic clots. Disclosures: M. Hafeez: None. M. Essibayi: None. D. Raper: None. S. Al Kasab: None. J. Burks: None. D. Alsbrook: None. M. Park: None. T. Dumont: None. R. Townsend: None. R. Starke: None. A. Arthur: None. N. Goyal: None. I. Maier: None. S. Wolfe: None. J. Mascitelli: None. K. Fargen: None. A. Spiotta: None. P. Kan: None.